Colony relatedness in aggregations of Apis dorsata Fabricius (Hymenoptera, Apidae). - Oldroyd, B. P.; Osborne, K. E.; Mardan, Makhdzir (Springer Verlag, 2000)
Apis dorsata colonies often form dense aggregations, with over 100 colonies sometimes seen in the same tree. Reasons for these aggregations are unknown, but one reasonable hypothesis is that colonies form a related family group. Here we show that 7 adjacent colonies sampled from a single branch of a tree (near Alor Setar in northern peninsular Malaysia) containing over 120 colonies were not related as mother/daughter. Thus the notion that aggregations arise through splitting of the first-arriving colonies can be rejected.